Isolation of subcellular fractions of Nuerospora of mycelio - K. D. Munkres; M. N. Munkres; P. Greens; S. Hedman; B. J. Andrews; G. Holland; D. O. Woodward (Fungal Genetics Reports, 1966)
Isolation of subcellular fractions